2002
DOI: 10.1051/animres:2002033
|View full text |Cite
|
Sign up to set email alerts
|

Foraging in patchy grasslands: diet selection by sheep and cattle is affected by the abundance and spatial distribution of preferred species

Abstract: -Understanding the distribution of grazing activity and its management is valuable to ensure the sustainability and productivity of heterogeneous grasslands. Controlled behavioural studies can provide insight into the cognitive abilities of herbivores and suggest new approaches to improve their grazing distribution. We compared the behaviour and diet selection of sheep and cattle in 1-ha fescue (Festuca arundinacea S.) plots, in which the number and size of preferred ryegrass (Lolium perenne L.) patches were v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 27 publications
4
69
2
2
Order By: Relevance
“…Understanding the type of plant species selected by the animal and the contribution of each species to the total intake could give an insight into the nutritional status of the animal and offer a feasible range management strategy to optimise resource utilisation (Dumont et al, 2002). However, measurement of feed intake, diet composition and nutrient digestibility in free-ranging animals remains a challenge in nutritional studies -E-mail: derseh7@yahoo.com because of the inherent errors associated with the methods that are used at present (Dove and Mayes, 1991;Mayes and Dove, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the type of plant species selected by the animal and the contribution of each species to the total intake could give an insight into the nutritional status of the animal and offer a feasible range management strategy to optimise resource utilisation (Dumont et al, 2002). However, measurement of feed intake, diet composition and nutrient digestibility in free-ranging animals remains a challenge in nutritional studies -E-mail: derseh7@yahoo.com because of the inherent errors associated with the methods that are used at present (Dove and Mayes, 1991;Mayes and Dove, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to sheep, cattle have lesser browsing ability because of their wider muzzle and other morpho-physiological characteristics. Cattle are mainly indiscriminate consumers of grass in the higher herbal layer while sheep are more selective grazers (Dumont et al 2002). As a consequence, in response to changing forage availability and phenological stages, different livestock species will behave differently (Stuth et al 1987).…”
Section: Variable Demand-foraging Behaviourmentioning
confidence: 99%
“…These three broad classification categories place all seed-bearing plants within three broad categories: grasses, forbs (herbaceous dicots commonly referred to as weeds) and woody plants (phenology can range from shrubs to trees depending on their response to effective precipitation and past management practices). It is from among these three plant categories, often found in a patchy mosaic (Dumont et al, 2002), that most domestic ruminant livestock select their diets. Browsers and grazers differ in their foraging behavior (Gordon, 2003).…”
Section: Aspects Of the Plant And Animal Interfacementioning
confidence: 99%
“…Recently, Laca (2009) suggested that when plant associations are 'less patchy' and 'well mixed' across a landscape, livestock apparently are less able to select a preferred diet. This phenomenon partially explains the heterogeneous use of large pastures (Vallentine, 1990) and the effect of plant spatial patterns on herbivore foraging (Anderson et al, 1985;Clarke et al, 1995;Hester et al, 1999;Dumont et al, 2002). Thus, understanding animal behavior is crucial to managing standing crop utilization.…”
Section: Aspects Of the Plant And Animal Interfacementioning
confidence: 99%